Cancer'S epicentre: Cancer stem cells - Pathak R.K.; Hangloo A.; Chaturvedi V.K.; Agarwal S.; Verma V.; Tabassum N.; Singh M.P. (My University, 2025)
Cancer stem cells (CSCs) are robust cells which may have acquired characteristics similar to the normal tissue stem cells. CSCs have a set of antigens or markers that define them as a cancer stem cell, which can facilitate isolation of relatively pure populations of these cells from heterogeneous tumors. Various signaling pathways like micro-RNAs and Wnt/β-catenin, Notch, and Hedgehog controls and regulates CSCs properties. CD 90 is a potential marker of liver CSCs. CD44, CD24 and CD133 are the cell surface markers which indicate the prosperity of CSCs and act as unique identifiers. CSCs are the source of many solid tumor types. This chapter will discuss about the cancer stem cell, its cell surface marker and the miscellaneous attributes of CSCs. © 2017 by Nova Science Publishers, Inc. All rights reserved.